The Influence of Self Efficacy and Job Satisfaction on Employee Performance in HR Management PT Mitra Adiperkasa - Kurniawan, Rania Apriella Putri; Saragih, Romat (PT FORMOSA CENDEKIA GLOBAL, 2024)
In order to better understand the impact of self-efficacy on PT Mitra Adiperkasa employees' performance, as well as the ways in which work satisfaction and self-efficacy interact with one another, this research will examine both variables alone and in combination. Topics addressed by this study's quantitative approaches include descriptive data analysis, causation, and the use of primers derived from surveys given to PT Mitra Adiperkasa's HR Management staff. Saturated sampling, in which 62 people are chosen at random from the whole population, was used for the sampling process. This study makes use of multiple linear regression as its method of data analysis. Both self-efficacy and work satisfaction are deemed positive by descriptive study. Simultaneous hypothesis testing, however, found that both self-efficacy and work satisfaction had an effect on productivity. Employee performance is partly influenced by the self-efficacy variable, according to this study's findings. The coefficient of determination shows that self-efficacy and work satisfaction account for 35.7% (or 0.357) of the variance in employee performance. At the same time, variables not included in the analysis account for 64.3% of the variance in employee performance.